Experiences of participation in integrated watershed development project in Himachal Pradesh - Negi, S.S. (2001)
The integrated watershed development project is a participatory, interdisciplinary venture being implemented in the Shiwalik hills of Northern India. There has been enthusiastic participation of local populace through Village Development Committees, each covering small micro-watersheds. The paper deals with the experiences in participatory approaches adopted by the project and focuses on the application of participatory strategies for tackling environmental problems in the Shiwalik hills which are one of the eight most degraded rainfed agro-eco systems of India. - Reproduced
Keywords: Watersheds - India - Himachal Pradesh; Watersheds